2022
DOI: 10.1038/s41398-022-01897-y
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in Alzheimer’s disease: a systematic review and meta-analysis of polysomnographic findings

Abstract: Polysomnography (PSG) studies of sleep changes in Alzheimer’s disease (AD) have reported but not fully established the relationship between sleep disturbances and AD. To better detail this relationship, we conducted a systematic review and meta-analysis of reported PSG differences between AD patients and healthy controls. An electronic literature search was conducted in EMBASE, MEDLINE, All EBM databases, CINAHL, and PsycINFO inception to Mar 2021. Twenty-eight studies were identified for systematic review, 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 88 publications
3
21
0
Order By: Relevance
“…This was comparable to those who were cognitively normal. Corroborating the consensus findings in AD, 8 we show that SWS is reduced in AD patients, but without seeing reductions in REM. Our findings address the limitations of PSG, especially cost, availability, and the need to spend a night in a hospital bed, while also addressing the main limitation of home EEG related to increased variability in data quality in the less controlled home environment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This was comparable to those who were cognitively normal. Corroborating the consensus findings in AD, 8 we show that SWS is reduced in AD patients, but without seeing reductions in REM. Our findings address the limitations of PSG, especially cost, availability, and the need to spend a night in a hospital bed, while also addressing the main limitation of home EEG related to increased variability in data quality in the less controlled home environment.…”
Section: Discussionsupporting
confidence: 85%
“…While most sleep disorders are addressed symptomatically, more recent studies are addressing biological links by which sleep disturbances directly impact AD pathophysiology, especially levels of brain amyloid beta (Aβ) and tau 3–7 . A number of small studies using laboratory polysomnography (PSG) testing in AD have reported reduced slow‐wave sleep (SWS) and rapid eye movement (REM) sleep, 8 both of which are potential sleep therapeutic targets. As the gold standard, PSG affords the highest quality sleep staging information, but with the major drawbacks of high cost, limited availability, and the requirement to spend a night in a clinic bed, with inherent risks to persons with dementia who do not respond well to a change in environment.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 Dysfunction of the sleep cycle in AD features sleep fragmentation with shorter slow‐wave sleep (SWS‐N3), excessive daytime sleepiness (EDS), and sundowning. 6 EDS is also associated with impaired cognitive functions in elderly individuals and patients with mild cognitive impairment. 7 Measurement of non‐rapid eye movement (NREM), slow wave activity (SWA), and sleep quality may predict the rate of Aβ and tau accumulation in the cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep cycle disturbances are a common symptom in the early stages of AD, 3 and epidemiological studies have shown a link between sleep problems and dementia 4,5 . Dysfunction of the sleep cycle in AD features sleep fragmentation with shorter slow‐wave sleep (SWS‐N3), excessive daytime sleepiness (EDS), and sundowning 6 . EDS is also associated with impaired cognitive functions in elderly individuals and patients with mild cognitive impairment 7 .…”
Section: Introductionmentioning
confidence: 99%
“… 44 Finally, alterations in REM-sleep duration, latency and synchrony have been reported in AD probably due to degeneration of basal forebrain cholinergic nuclei. 45 46 However, the potential diagnostic usefulness of REM and NREM-sleep alterations in preclinical AD remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%